2019
DOI: 10.5688/ajpe6976
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Components of Success Within Health Sciences-Focused Mentoring Programs Through a Review of the Literature

Abstract: Objective. To identify programmatic components and structural features associated with success of mentoring programs within the health sciences. Findings. Thirty-eight manuscripts representing 34 individual programs were reviewed. Of the institutions represented, 68% were public. Sixty-eight percent of programs included single disciplines only, with four focused in pharmacy, 13 in medicine, and six in nursing. Of the 34 individual programs, all programs reporting participant confidence and self-efficacy report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…McRae and Zimmerman recently conducted a systematic review of health sciences‐focused mentoring programs to identify specific components and structures associated with programmatic success 100 . The review identified the importance of routine engagement with mentorship programs that demonstrate success on the basis of scholarship that was met on a monthly basis, at minimum.…”
Section: Part 2: Updates In Faculty Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…McRae and Zimmerman recently conducted a systematic review of health sciences‐focused mentoring programs to identify specific components and structures associated with programmatic success 100 . The review identified the importance of routine engagement with mentorship programs that demonstrate success on the basis of scholarship that was met on a monthly basis, at minimum.…”
Section: Part 2: Updates In Faculty Developmentmentioning
confidence: 99%
“…More than 70% of faculty are older than 40, so regardless of definition, those advanced in their career account for most of the faculty workforce. In contrast, most mentoring and development programs target junior faculty, and many schools have inadequate local resources for mentorship of senior faculty and faculty administrators 100,101 . In academic medicine, mid‐career faculty experience significant declines in mentorship relationships and professional development opportunities 102 .…”
Section: Part 2: Updates In Faculty Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Although formal mentoring programs may require more resources, benefits include higher rates of faculty retention due to the structure and curriculum of the program and commitment from the mentee, mentor, and institution. 1,[13][14][15] In a recent review of faculty mentoring programs, McRae and colleagues 1 identified only four papers describing formal programs within schools of pharmacy. The described programs utilized various formats and approaches, including external faculty mentoring, 14,16 department mentoring, 17 multi-institution mentoring, 18 and voluntary mentoring.…”
Section: Introductionmentioning
confidence: 99%
“…Faculty engagement in clinical service, education, and research is the cornerstone of academic health centers and is facilitated by faculty development opportunities at their home institutions. [3][4][5][6][7] Senior faculty are frequently invited to give presentations at other institutions, provide plenary sessions at conferences, serve on grant review boards, and assume leadership roles within professional organizations, but junior faculty have fewer opportunities. Faculty exchange programs, particularly those designed with junior faculty in mind, provide junior faculty with the opportunity to meet established researchers with similar interests outside of their own universities, develop new research collaborations, engage in joint publications, and increase their professional networks and visibility.…”
Section: Introductionmentioning
confidence: 99%